2020
DOI: 10.1002/med.21743
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the adaptogenic concept from traditional use to medical systems: Pharmacology of stress‐ and aging‐related diseases

Abstract: Adaptogens comprise a category of herbal medicinal and nutritional products promoting adaptability, resilience, and survival of living organisms in stress. The aim of this review was to summarize the growing knowledge about common adaptogenic plants used in various traditional medical systems (TMS) and conventional medicine and to provide a modern rationale for their use in the treatment of stress‐induced and aging‐related disorders. Adaptogens have pharmacologically pleiotropic effects on the neuroendocrine‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
145
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 209 publications
(162 citation statements)
references
References 501 publications
(1,196 reference statements)
4
145
0
13
Order By: Relevance
“…It has often been reported that a CHM herbal constituent exhibits multiple effects in the pathogenesis of depression [ 200 , 201 , 202 ]. Several representative CHM constituents that have been shown to exert multiple actions on the neuroendocrine-immune network are shown in Figure 4 .…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 99%
“…It has often been reported that a CHM herbal constituent exhibits multiple effects in the pathogenesis of depression [ 200 , 201 , 202 ]. Several representative CHM constituents that have been shown to exert multiple actions on the neuroendocrine-immune network are shown in Figure 4 .…”
Section: Chm Effects On the Neuroendocrine-immune Networkmentioning
confidence: 99%
“…It is noteworthy that several adaptogenic plants have been used in medical species. Besides the common properties of promoting the adaptability, resilience, and survival of living organisms under stress ( Panossian et al, 2021 ), each adaptogen has some specific activity. In particular, Oplopanax elatus (Nakai) Nakai lowered blood glucose and increased insulin levels in vivo ( Molokovskii et al, 2002 ).…”
Section: Resultsmentioning
confidence: 99%
“…The rationality of mixing different herbs with a certain ratio was also verified with statistical significance in vitro and in vivo. The synergy principles for herbal mixtures are common for adaptogens (Panossian et al, 2021) and traditional Indian systems of medicine (Mukherjee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Along with the increase in urbanization and industrialization, the rapid pace of living and a high-pressure society have placed more and more people in extended periods of anxiety, tension, insomnia, and melancholy. These signs are characteristic of a state of decreased resistance to stress, which could be ameliorated by adaptogens (Panossian et al, 2021). These symptoms of suboptimal health are also commonly associated with the above Shang-huo indicators of TCM, which are actually similar to the phenomena of topical inflammation in immunology (Pan et al, 2020).…”
Section: Introductionmentioning
confidence: 97%